PENGARUH EKSTRAKURIKULER KEPRAMUKAAN TERHADAP PERUBAHAN KARAKTER MAHASISWA PRODI PGSD UNIVERSITAS MEGAREZKY - Nurti Datulengken; Eka Fitriana HS; Jalal; Waddi Fatimah (Jurnal Binagogik, 2024)
This study aims to determine the effect of scouting extracurriculars on changes in the character of PGSD study program students at Megarezky University. This type of research is quantitative and uses the ex post facto method. The population in this study was all students of the 2019 and 2021 batches in the Megarezky University Scout UKM, consisting of 98 students. The samples in this study were the 2019 class. 15 students, and the 2021 class, 15 students, who were obtained using the simple random sampling technique. The instrument used is a questionnaire. The results of the study used descriptive and inferential statistical analysis using SPSS 20 for Windows.Based on the descriptive analysis, it is shown that the average value of scouting extracurriculars is 73.60, which is in the good category, and the average value of character change is 69.63, which is also in the good category. Financial stratistic analysis showed that the normality test for scouting extracurriculars were 0.205 and character changes were 0.059>0.05 (normal distribution), the results for scouting extracurricular homogeneity tests were 0.873>0.05 (homogeneous), and the linear extracurricular test results for scouting were 0.127>0.05 Thus, there is a linear relationship between scouting extracurriculars and changes in character. The results of the hypothesis test showed a sig value of 0.001, with the criteria of sig (0.001) (0.05). The conclusion in this study is that there is an influence of extracurricular scouting on changes in the character of PGSD study program students at Megarezky University.